Crosstalk Between Dermal Fibroblasts and Dendritic Cells During Dengue Virus Infection - Montes-Gómez, Alfredo E.; García-Cordero, Julio; Marcial-Juárez, Edith; Shrivastava, Gaurav; Visoso-Carvajal, Giovani; Juárez-Delgado, Francisco J.; Flores-Romo, Leopoldo; Sanchez-Torres, Ma. Carmen; Santos-Argumedo, Leopoldo; Bustos-Arriaga, José; Cedillo-Barrón, Leticia (Frontiers in Immunology, 2020)
Dengue virus infection (DENV-2) is transmitted by infected mosquitoes via the skin, where many dermal and epidermal cells are potentially susceptible to infection. Most of the cells in an area of infection will establish an antiviral microenvironment to control viral replication. Although cumulative studies report permissive DENV-2 infection in dendritic cells, keratinocytes, and fibroblasts, among other cells also infected, little information is available regarding cell-to-cell crosstalk and the effect of this on the outcome of the infection. Therefore, our study focused on understanding the contribution of fibroblast and dendritic cell crosstalk to the control or promotion of dengue. Our results suggest that dendritic cells promote an antiviral state over fibroblasts by enhancing the production of type I interferon, but not proinflammatory cytokines. Infected and non-infected fibroblasts promoted partial dendritic cell maturation, and the fibroblast-matured cells were less permissive to infection and showed enhanced type I interferon production. We also observed that the soluble mediators produced by non-infected or Poly (I:C) transfected fibroblasts induced allogenic T cell proliferation, but mediators produced by DENV-2 infected fibroblasts inhibited this phenomenon. Additionally, the effects of fibroblast soluble mediators on CD14+ monocytes were analyzed to assess whether they affected the differentiation of monocyte derived dendritic cells (moDC). Our data showed that mediators produced by infected fibroblasts induced variable levels of monocyte differentiation into dendritic cells, even in the presence of recombinant GM-CSF and IL-4. Cells with dendritic cell-like morphology appeared in the culture; however, flow cytometry analysis showed that the mediators did not fully downregulate CD14 nor did they upregulate CD1a. Our data revealed that fibroblast-dendritic cell crosstalk promoted an antiviral response mediated manly by type I interferons over fibroblasts. Furthermore, the maturation of dendritic cells and T cell proliferation were promoted, which was inhibited by DENV-2-induced mediators. Together, our results suggest that activation of the adaptive immune response is influenced by the crosstalk of skin resident cells and the intensity of innate immune responses established in the microenvironment of the infected skin.